Mapping Jewish Loyalties in Interwar Slovakia - Klein-Pejšová, Rebekah, 1972- (Book collections on Project MUSE., 2015)
In the aftermath of World War I, the largely Hungarian-speaking Jews in Slovakia faced the challenge of reorienting their political loyalties from defeated Hungary to newly established Czechoslovakia. Rebekah Klein-Pejšová examines the challenges Slovak Jews faced as government officials, demographers, and police investigators continuously tested their loyalty. Focusing on ""Jewish nationality"" as a category of national identity, Klein-Pejšová shows how Jews recast themselves as loyal citizens of Czechoslovakia. Mapping Jewish Loyalties in Interwar Slovakia traces how the interwar state saw a.